Curious, Collaborative, Creativity: Applying Student-Centered Principles to Performing Ensembles. (December 2016) - Gilbert, Danni
This article explores a comprehensive, student-centered alternative to traditional ensemble instruction with the goal of promoting better opportunities for musical independence and lifelong musicianship. Developed by Caron Collins from the Crane School of Music at the State University of New York-Potsdam, the Curious, Collaborative, Creativity (CCC) concept fosters student-centered learning and the promotion of 21st-century skills by encouraging students to select, arrange, and compose the repertoire to be studied; to work together in teams to equally contribute to the learning/understanding of music; and to share their work through informances to engage and enlighten community members. Examples from a current ensemble practicing CCC ideas illustrate the implementation of the model and provide suggestions for music educators.